2007
DOI: 10.1177/112070000701700304
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Term Follow-Up Series Using a Modular Distal Fixation Prosthesis to Address Proximal Femoral Bone Deficiency in Revision Total Hip Arthroplasty. A 5- to 9-Year Follow-Up Study

Abstract: We reviewed a series of 39 patients (40 cases) receiving the Link MP stem in revision hip arthroplasty. Average follow-up was 68 months (range 60-115 months). Proximal femoral defects were classified using the Endo-Klinik and Paprosky classifications. Indications included: osteolysis 13 cases; septic loosening 8 cases; periprosthetic fractures 18 cases; metastatic bone disease 1 case. We found 92.5% overall survival rate, average Harris Hip Score past two years of 67 and average Oxford Hip Score past five year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several designs of tapered and modular fluted stems have been developed. The aim is to provide immediate axial and rotational stability distally in the femur, where the bone is less compromised by the loosening process (Wirtz et al 2000, Kwong et al 2003, Schuh et al 2004, McInnis et al 2006, Tamvakopoulos et al 2007, Rodriguez et al 2009, Weiss et al 2009). In revisions, bone loss and deformity are not always predictable.…”
mentioning
confidence: 99%
“…Several designs of tapered and modular fluted stems have been developed. The aim is to provide immediate axial and rotational stability distally in the femur, where the bone is less compromised by the loosening process (Wirtz et al 2000, Kwong et al 2003, Schuh et al 2004, McInnis et al 2006, Tamvakopoulos et al 2007, Rodriguez et al 2009, Weiss et al 2009). In revisions, bone loss and deformity are not always predictable.…”
mentioning
confidence: 99%
“…The use of modular femoral stems is presented by many authors in demanding cases of hip reconstruction such as congenital dysplastic hip and revision arthroplasty [16,17]. The use of a calcar-replacement and/or a modular implant should be considered for challenging cases of hip reconstruction even after failed peritrochanteric treatment [18].…”
Section: Discussionmentioning
confidence: 99%
“…Implant failure (modular junction) was no problem in our series, which is in accordance with other studies. Tamvakopoulos et al [ 13 ] reported comparable findings with an overall survival of 92.5% of the MP system at an average follow-up of 5.6 years in 40 cases. Kwong et al [ 8 ] evaluated 143 patients at an average of 3.3 years with 97% component survival using the same stem.…”
Section: Discussionmentioning
confidence: 63%